DISEMINASI PENTINGNYA PERLINDUNGAN HIUS PAUS BAGI MASYARAKAT PESISIR PERAIRAN BATANG, KABUPATEN JAWA TENGAH - Wiwid Andriyani Lestariningsih; Mahardika Rizqi Himawan; Afid Wisnubroto (Universitas Mataram, 2023)
The diversity of marine biota functions to support a healthy and sustainable food chain. The beauty and attractiveness of tourism, along with the role of marine biota, make a significant contribution to economic growth and community welfare in coastal areas. One of the marine biotas that is currently the center of attention is the whale shark. Whale sharks have an economic impact on coastal communities in terms of ecotourism. The aim of this research is to increase knowledge and awareness among coastal communities regarding the sustainability of marine biota, especially whale sharks, through dissemination. This dissemination activity took place on August 23-24, 2023. The method used in this community service involved delivering materials and engaging in direct question-and-answer discussions with the community, where PowerPoint presentations (PPTs) and leaflets were utilized as tools to assist in delivering the material. The target audience consisted of 72 people, including fishermen, extension workers, related agencies, government officials, industry representatives, and members of the media. The outcome of this activity is an increased level of information and knowledge (awareness) among the target audience regarding the sustainability of marine biota, especially whale sharks.